From Verse to Praxis: An Eco-Theological Exegesis of Qur'anic Educational Verses for a Love-Based Pedagogy - Rohman, Muhamad Asvin Abdur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Thisarticle aims to examine the concept of love-based education in the Qur'an through an eco-theological interpretation of educational verses.In this study, theconcept of